32. KNOWLEDGE AND PRACTICES ON FOOD SAFETY AMONG FOOD PROCESSORS IN THAI BINH PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to describe the current status of knowledge and practices regarding food safety among food producers and processors in Thai Binh province in 2023.Subject and methods: A cross-sectional study involving 251 individuals directly involved in food production and processing in Thai Binh province in 2023 to assess their knowledge and practices regarding food safety.Results: 92.4% of food producers and processors demonstrate adequate food safety knowledge. In urban areas, compliance is 87.9% (31.3% level A, 56.6% level B), while rural areas show 95.4% (32.2% level A, 63.2% level B). Correct practices are observed at an overall rate of 97.6%, with urban areas at 99% (63.6% level A, 35.4% level B) and rural areas at 96.7% (61.8% level A, 34.9% level B). Areas needing improvement include regulations on food additives (63.7%), understanding consequences of improper food storage (65.3%), and practices like smoking or chewing gum during production (7.2%), improper attire (16.7%), and compliance with safety gear during food processing (76.5%).Conclusion: The overall knowledge attainment among food producers and processors is high at 92.4%, with urban and rural areas showing similar rates. However, achieving level A (≥ 80% correct) is relatively low at 31.9% (31.2% urban, 32.2% rural). Practical application rates are also high at 97.6%, with a larger proportion achieving level A (> 60%) in both areas. Enhanced training and educational outreach in health and food safety communication are essential to further improve practices in this sector.
Keywords: Food safety, knowledge, practice, production, Thai Binh.